Medication use and the risk of motor vehicle collisions among licensed drivers: A systematic review - Rudisill, Toni M. (Accid Anal Prev, 2016)
OBJECTIVES: Driving under the influence of prescription and over-the-counter medication is a growing public health concern. A systematic review of the literature was performed to investigate which specific medications were associated with increased risk of motor vehicle collision (MVC). METHODS: The a priori inclusion criteria were: 1) studies published from English-language sources on or after January 1, 1960, 2) licensed drivers 15 years of age and older, 3) peer-reviewed publications, master's theses, doctoral dissertations, and conference papers, 4) studies limited to randomized control trials, cohort studies, case-control studies, or case-control type studies 5) outcome measure reported for at least one specific medication, 6) outcome measure reported as the odds or risk of a motor vehicle collision. Fourteen databases were examined along with hand-searching. Independent, dual selection of studies and data abstraction was performed. RESULTS: Fifty-three medications were investigated by 27 studies included in the review. Fifteen (28.3%) were associated with an increased risk of MVC. These included Buprenorphine, Codeine, Dihydrocodeine, Methadone, Tramadol, Levocitirizine, Diazepam, Flunitrazepam, Flurazepam, Lorazepam, Temazepam, Triazolam, Carisoprodol, Zolpidem, and Zopiclone. CONCLUSIONS: Several medications were associated with an increased risk of MVC and decreased driving ability. The associations between specific medication use and the increased risk of MVC and/or affected driving ability are complex. Future research opportunities are plentiful and worthy of such investigation.